(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Although shoes are conventionally chosen based on the size indicated on the label, it is also possible to accurately gauge foot size using a technique known as morphometry to measure the three-dimensional shape of feet in a state of rest. However, because shoe sizes differ slightly for each shoe manufacturer despite the use of a standardized labeling system, there is no guarantee that consumers will be able to choose a pair of shoes that properly fit the size of their feet. Furthermore, some consumers are in the habit of wearing larger shoes to accommodate the width of their feet. The purpose of this study was to develop a quantitative understanding of the relationship between shoe size (foot length) and gait by using techniques such as electromyogram of the lower leg, measurement of ground reaction force, and subjective evaluation. The subjects, five male university students with no history of leg injury, all had a foot length of 26.5 cm and a foot width of size D as defined by JIS standards. Prior to the experiment, the subjects' consent were obtained after briefing them on anticipated risks and safety considerations, management of their personal information, and other aspects of the study. Experimental samples consisted of a total of five D-width shoes in sizes ranging from 26.0 cm to 28.0 cm, in 0.5 cm increments. Each subject was fitted with an electromyogram measuring device on the gastrocnemius and tibialis anterior muscles on his right leg, and a plantar pressure distribution measuring sheet was placed in each of the sample shoes. Each subject took 10 strides while wearing each sample shoe along a predetermined route in the lab, under which a device for measuring floor reaction force had been installed. After each subject had walked in each shoe sample, they filled out a questionnaire on the sensations experienced while walking. When the shoe size (foot length) was at least 1 cm longer than the subject's proper size, a significant increase in activity by the gastrocnemius muscle was noted along with a significant decrease in the floor reaction force value (F2) at kick-off. These changes were attributed to the psychological effects of factors such as ease of kick-off. The findings suggest that the parameters used in this study, including muscular activity level, floor reaction force peak value, and gait reproducibility, have the potential to serve as useful indicators in evaluating the functional compatibility between shoe wearers and shoe size.